CHARACTERIZATION AND EFFECTIVENESS OF MORINGA OLEIFERA SEEDS EXTRACT AS A PHOSPHATE COAGULANT - Yulianti, Eny; Istighfarini, Vina Nurul; Lutfia, Fadilah Nor Laili; Sya’banah, Nishfu (Jurnal Neutrino:Jurnal Fisika dan Aplikasinya, 2020)
In this research, Moringa oleifera seeds extract has been shown the ability as a coagulation agent. The molecules that act as the coagulation agents were the proteins which were obtained by the extraction process of the Moringa seeds using NaCl solution. The aim of this research was to characterize and test the effectiveness of the Moringa seeds extract as a phosphate coagulant. The determination of the coagulation process was carried out using a Jar Test method of phosphate solution samples, and then effectiveness the samples were analyzed using a UV-Vis spectroscopy after-treatment of the coagulant dose variations, depositional time, and the pH variations of the samples. The characterization of the extract functional groups was determined using an FTIR spectroscopy. The results of the coagulation phosphate sample examinations showed that the optimum dose of the coagulant was 80 mL/L, with a decrease in the initial phosphate concentration of 17 ppm to 13.58 ppm. The reduction effect of precipitation time and pH also was obtained in this research. The optimum precipitation time and pH were in 30 minutes and pH 8, which reduced the phosphate concentration to 11.697 and 9.6 ppm, respectively. The FTIR spectra of Moringa oleifera seeds extracts before and after interacting with phosphate showed their differences. The interactions between the extract and phosphate were demonstrated by the appearance of buckling vibrations at wavenumbers 1064.2 cm-1, 799.8 cm-1, and 668.8 cm-1. The results of this study indicated that the Moringa seeds extraction with NaCl has potential as a phosphate coagulation agent.